Argument relevance and structure. Assessing and developing students' uses of evidence. (2016) - Macagno, Fabrizio
Highlights: Defining and coding argument relevance. Analyzing the relationship between argument-as-a-product and argument-as-a-process. Developing two coding schemes for analyzing argument structure and relevance. Assessing the impact of the dialogical mode on students' use of evidence. Abstract: The purpose of this paper is to show whether the two crucial dimensions used for assessing the quality of argumentation, argument-as-a-product (argument structure) and argument-as-a-process (relevance), are interrelated, and how they can be used to assess the effect of argumentative mode on students' arguments. To this purpose, a twofold coding scheme will be developed, aimed at capturing: a) the argumentative function of evidence use and b) the dialogical relevance of evidence use. A study will be described in which students' use of evidence is elicited in two distinct argumentative modes (dialogical vs. non-dialogical). According to the results, in the dialogical mode students tended to use evidence in a more sophisticated way from both argument evaluation perspectives.